"SUSTAINABLE DEVELOPMENT THROUGH NATIONAL EDUCATION POLICY-2020" (International Journal of Food and Nutritional Sciences, 2022)
The world is on the verge of 'The Fourth Industrial Revolution and India must take advantage of it to reach new heights in the global economy. National Education Policy 2020, recently launched education policy, which may transform the entire spectrum of education and convert it into an egalitarian and vibrant knowledge society by providing high-quality education to all citizens. To achieve the "Sustainable Educational Goal", introduced by UNESCO and United Nations Organization in 2017, worldwide modifications and changes have been taken place by the respective countries. Sustainable Educational Goals are an integral part of Sustainable Development Goals-2030, set by UNESCO and UNO. Education for Sustainable Development is a key element of the SDG-2030. It has given huge importance to the 'Education Sustainable Goal' (SDG-4) to achieve all other 17 SDGs. It empowers environmental integrity, economic viability, and just society, which will be helpful for human beings. Educational Sustainable Development aims to address development challenges by providing the knowledge, skill, attitude, and values necessary. Learning objectives and guidelines of the 'Education Sustainable Goal' have been set by UNESCO, and supportive information and resources have been designed for the stakeholders, educators, Planners, etc. To implement these ESD goals through the educational institutions to develop the required skill set from early childhood care and secondary education. The National Education Policy-2020 has accepted and adopted almost all objectives of SDG-2030, by introducing educational reforms, modifications, and introduction of new ideas. This paper attempts to elaborate on NEP-2020 and future educational sustainable development-related prospects and issues. Also, suggest a pathway to sustainable development through implementation strategies, and agenda for an action plan for socio-economic concerns of education